Arctic and Subarctic Construction. General Provisions. - Lobacz,Edward F (1986)
Working in the world's cold regions is quite different from working in warmer places. This document gives general information on frost action, permafrost and other special factors to help engineers who must operate in arctic and subarctic areas. Keywords: Arctic regions, Construction, Military engineering, Subarctic regions, Military facilities, Army, Air Force.